Studying the effect of chitosan as drag reducing agent in water flowing systems with different concentration and preparation using different acid types - Nur Khadijah, Mohamad Najib (2009)
The investigation of turbulent drag reduction, which is caused by the addition of a small amount of polymer or some other substances to the liquids flowing systems has been the focus of attention of many scientists for the last decades. Due to the reduction of the drag, pumping power for the pipeline will significantly reduced and thus will decrease the cost of electricity in total production cost. It also has great impending in the industrial applications, such as in liquid pipeline transportation. In the present work, a new drag reducing agent has been devised from natural occurring polymer based which is Chitosan. The polymer additive prepared is tremendously cheaper compared to other commercial drag reducing agents and nevertheless offering the comparable performance in reducing drag. The method of preparation the additive is uncomplicated, not time consuming and most of the compound used are fulfilling natural need. Two types of chitosan solution is prepared using different types of acid and three different proportion of volume in the solution and each solution are measured in term of viscosity The turbulent drag reductions are measured by reading the value of pressure drop along the pipeline re-circulatory flow system of approximately 400 kg tap water. A drastic reduction of drag in the turbulent flow of solutions as appraised with pressure drop reduction in comparison to the pure solvent can be observed, even when only minute amounts of the additives are added. The % of drag reduction is relatively increases as the increases concentration of polymer DRA. Approximately 80.842% of maximum drag reductions for solution prepared with hydrochloric acid are obtained before no more reductions can be achieved as it reached concentration limits. the drag maximum drag reduction point for this type of solution are slightly higher than solution prepared with acetic acid but shows the drastic reduction in %DR.